Respiratory modulation of human autonomic function on Earth. (26th July 2016) - Eckberg, Dwain L.; Cooke, William H.; Diedrich, André; Biaggioni, Italo; Buckey, Jay C.; Pawelczyk, James A.; Ertl, Andrew C.; Cox, James F.; Kuusela, Tom A.; Tahvanainen, Kari U. O.; Mano, Tadaaki; Iwase, Satoshi; et al.
Abstract : Key points: We studied healthy supine astronauts on Earth with electrocardiogram, non‐invasive arterial pressure, respiratory carbon dioxide concentrations, breathing depth and sympathetic nerve recordings. The null hypotheses were that heart beat interval fluctuations at usual breathing frequencies are baroreflex mediated, that they persist during apnoea, and that autonomic responses to apnoea result from changes of chemoreceptor, baroreceptor or lung stretch receptor inputs. R‐R interval fluctuations at usual breathing frequencies are unlikely to be baroreflex mediated, and disappear during apnoea. The subjects' responses to apnoea could not be attributed to changes of central chemoreceptor activity (hypocapnia prevailed); altered arterial baroreceptor input (vagal baroreflex gain declined and muscle sympathetic nerve burst areas, frequencies and probabilities increased, even as arterial pressure climbed to new levels); or altered pulmonary stretch receptor activity (major breathing frequency and tidal volume changes did not alter vagal tone or sympathetic activity). Apnoea responses of healthy subjects may result from changes of central respiratory motoneurone activity. Abstract: We studied eight healthy, supine astronauts on Earth, who followed a simple protocol: they breathed at fixed or random frequencies, hyperventilated and then stopped breathing, as a means to modulate and expose to view important, but obscure central neurophysiological mechanisms. Our recordings included the electrocardiogram, finger photoplethysmographic arterial pressure, tidal volume, respiratory carbon dioxide concentrations and peroneal nerve muscle sympathetic activity. Arterial pressure, vagal tone and muscle sympathetic outflow were comparable during spontaneous and controlled‐frequency breathing. Compared with spontaneous, 0.1 and 0.05 Hz breathing, however, breathing at usual frequencies (∼0.25 Hz) lowered arterial baroreflex gain, and provoked smaller arterial pressure and R‐R interval fluctuations, which were separated by intervals that were likely to be too short and variable to be attributed to baroreflex physiology. R‐R interval fluctuations at usual breathing frequencies disappear during apnoea, and thus cannot provide evidence for the existence of a central respiratory oscillation. Apnoea sets in motion a continuous and ever changing reorganization of the relations among stimulatory and inhibitory inputs and autonomic outputs, which, in our study, could not be attributed to altered chemoreceptor, baroreceptor, or pulmonary stretch receptor activity. We suggest that responses of healthy subjects to apnoea are driven importantly, and possibly prepotently, by changes of central respiratory motoneurone activity. The companion article extends these observations and asks the question, Might terrestrial responses to our 20 min breathing protocol find expression as long‐term neuroplasticity in serial measurements made over 20 days during and following space travel? Key points: We studied healthy supine astronauts on Earth with electrocardiogram, non‐invasive arterial pressure, respiratory carbon dioxide concentrations, breathing depth and sympathetic nerve recordings. The null hypotheses were that heart beat interval fluctuations at usual breathing frequencies are baroreflex mediated, that they persist during apnoea, and that autonomic responses to apnoea result from changes of chemoreceptor, baroreceptor or lung stretch receptor inputs. R‐R interval fluctuations at usual breathing frequencies are unlikely to be baroreflex mediated, and disappear during apnoea. The subjects' responses to apnoea could not be attributed to changes of central chemoreceptor activity (hypocapnia prevailed); altered arterial baroreceptor input (vagal baroreflex gain declined and muscle sympathetic nerve burst areas, frequencies and probabilities increased, even as arterial pressure climbed to new levels); or altered pulmonary stretch receptor activity (major breathing frequency and tidal volume changes did not alter vagal tone or sympathetic activity). Apnoea responses of healthy subjects may result from changes of central respiratory motoneurone activity.